The Influences of Tax Knowledge, Tax System, Self-Assessment System, and Tax Morale on Tax Compliance - Hantono (Journal of Research in Business, Economics, and Education, 2021)
This study aims to determine the effect of 1) tax knowledge, 2) tax system, 3) self-assessment system, 4) tax morale, 5) tax compliance. The sampling in this research was conducted by using a incidental sampling method. Methods of data collection through questionnaires that have been distributed to 72 respondents who have met criteria. With multiple linear regression analysis, it shows that the tax knowledge, tax system, self-assessment system, tax morale both partial and simultaneous have significant effect on tax compliance. It can be concluded that mitigation of tax knowledge, tax system, self-assessment system, tax morale towards tax compliance. The results of t test showed that tax knowledge is approved and indicates tax knowledge has great impact on affecting the tax compliance, tax system is not approved and indicates tax system has less impact on affecting the tax compliance, self-assessment system is approved and indicates self-assessment system has great impact on affecting the tax compliance, tax morale is approved and indicates tax morale has great impact on affecting the tax compliance. The results of f test showed that both independent variables are simultaneously affecting the tax compliance. The result of R Square of the regression model is 0.807 which shows that 80.7 % of mitigation of the tax compliance can be explained by tax knowledge, tax system, self-assessment system, tax morale. Whereas the 19.3% of the tax compliance variable can be explained by other factors or variables which are not examined in this research.